Allelopathic Effects of Some Common Weeds Prevailing in Wheat Fields on Growth Characteristics of Wheat (Triticum aestivum L.) - Siyar, Saira; Chaudhry, Zubeda; Hussain, Fida; Hussain, Zahid; Majeed, Abdul (PSM Biological Research, 2017)
In this study, aqueous extracts of aerial parts of four common weeds (Avena fatua, Phalaris minor, Melilotus alba and Chenopodium album) found in cultivated fields of district Peshawar were tested for their allelopathic effects on wheat in seed bioassay. Extracts of each weed were applied at concentration 6, 8, 10 and 12 g/100 ml. Seeds germination and growth attributes of wheat such as radicle and plumule heights were significantly retarded under respective allelopathic aqueous extracts of all the tested weeds except M. alba which showed slight phyto-inhibition at the highest dose (12 g/100 ml) only; however, significant variation were observed among the weeds for their phyto-toxic behavior. In general, deleterious effects on germination and growth were found to be linearly correlated with concentration of extracts. Moreover, C. album was found more phyto-toxic followed by A. fatua and P. minor respectively. Least phytotoxicity was shown by the aqueous extracts of M. alba which had negative effects only at higher concentration.